Clinical and immunological characteristics of post-COVID syndrome - E. V. Zhdanova; E. V. Rubtsova; E. G. Kostolomova (Бюллетень сибирской медицины)
Aim. To evaluate changes in clinical manifestations and the cytokine profile of blood serum in patients with postCOVID syndrome. Materials and methods. The study involved 46 patients (37 women and 9 men) with signs of post-COVID syndrome 1–12 months after COVID-19 infection. COVID-19 infection was laboratory-confirmed (patients were tested positive for SARS-Cov-2 RNA using polymerase chain reaction (PCR), or they were tested positive for SARS-Cov-2 immunoglobulin (Ig)G antibodies after the end of the acute phase and in asymptomatic infection). Along with mandatory tests included in the regular health checkup of medical staff, the levels of interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-17, tumor necrosis factor alpha (TNFα), interferon gamma (INFγ), and total IgE were determined in the blood serum of patients. Results. The results showed that the development of post-COVID syndrome did not depend on the age and gender of patients and the severity of the acute phase of infection. Patients were more likely to develop postCOVID syndrome in the absence of antiviral therapy or in case of its ineffectiveness. A high level and imbalance of pro- and anti-inflammatory cytokines without laboratory signs of inflammation underlie the development of clinical manifestations at early stages of post-COVID syndrome (up to 3 months). The clinical presentation was characterized by symptoms of asthenia and functional disorders in the nervous, cardiovascular, and respiratory systems and gastrointestinal tract. After 3 months, the content of most cytokines returned to normal levels, whereas only the concentration of IL-17 remained elevated. Allergic and autoallergic mechanisms of damage to the skin, respiratory organs, and joints, as well as progression of cardiovascular pathology determined the clinical symptoms of post-COVID syndrome for 3–12 months. Conclusion. The changes in the cytokine profile over 12 months reflect different damage mechanisms at different periods of the post-COVID syndrome, which determines the range of its clinical manifestations.